THE “CONCEPT” IN LINGUISTICS (Scientific journal of the Fergana State University, 2024)
This article discusses the concept and its meanings, as well as similarities and differences of “concept” usage in linguistic, philosophical and logical dictionaries. Besides it discusses the definitions given to the term "concept" by linguists conducting research in Uzbek and Russian linguistics. It thoroughly discusses that the concept as a term has become the main object of research not only in linguistics but also in other fields, including philosophy, logic, linguistic and cultural studies, and that it is considered as a term that gives the central idea.